Opţiunea pentru strategii inovative în managementul strategic al organizaţiilor publice, nonprofit şi politice din România - Boboc, Ion (Calitatea Vieții, 2009)
The study refers to the results of a concrete research which monitored the intentions of public, non-profit and political organizations in Romania to initiate and develop innovative strategies in their strategic management, comparative with traditional or mixed strategies, in according to the classification made by American researchers Miles and Snow regarding strategic management (1978). In this regard, research was conducted in the summer of 2008 (July– September), by using several methods, such as: 1. field inqueries, based on cantitative instruments (questionnaires); 2. quality studies: non-directed interviews and focus groups; 3. the study of documents. Practically, our investigations focused on a certain domain of activity, which is innovative strategic management in public, non-profit and political organizations. In this regard, using the questionnaire sent through e-mail as an instrument for 115 subjects, we have investigated the innovative strategic management of public (22 youth councilors and directors from County Departments for Youths – DJT, and 28 youth councilors and directors in County Offices for Agricultural Consultancy – OJCA), associative agricultural formations (49 associations, cooperatives and producer groups), and nongovernmental and political organizations (other 14 NGO managers, including two leaders of political parties). Finally, we have used the case study method, applied in Buzau County, for DJT, OJCA, 10 NGO managers, including two political organizational leaders who had rezidency and activities in this county.